Determination of Smartphone Users’ Perceptions of Branded Mobile Applications in Turkey - Gumus, Niyazi (Bastas Publications, 2017)
Having numerous features thanks to advancements in digital technology, smartphones make life easier for users who today can conduct their activities and transactions independently of time and place by using a wide range of branded mobile applications (apps) on sports, finance, shopping and health etc. Through these apps, brands have the opportunity to reach users directly, interact with them and make customized offers. In order for brands to maximize their benefits from their own mobile apps, it is undoubtedly necessary to find out about smartphone users’ perceptions of those branded mobile apps. Therefore, the aim of this study is to determine smartphone users’ perceptions of branded mobile apps. In line with this purpose, face-to-face surveys were conducted in November-December 2016 with 437 students from Kastamonu University. Based on the results, smartphone users’ perceptions of branded mobile apps were grouped under the factors of facilitation, stimulation of purchase desire, customization and post-purchase trust.